Pergantungan Pendidikan dan Bahasa di Malaysia Satu Kajian Awal Terhadap Krisis Perspektif Berhubung dengan Peranan Bahasa Inggeris - Md. Jadi, Haris (Penerbit Universiti Sains Malaysia, 1984)
This essay attempts to provide relevance on the issue of educational dependency in the Third World countries today, taking Malaysia as a case. The essay argues that 'dependency' was the outcome of a long colonial cultural penetration and the imposition of colonial norms and values through various agencies and of particular importance was education. In Malaysia, the remnant of colonial cultural penetration still remains and this is manifested in the important role given to the English language in various facets of life. The over-emphasis given to this colonial language, creates a crisis of perspective over its function and role in the country. Besides undermining the position of the national language as the sole language of instruction in schools, the continued importance placed on the English language is also detrimental to the process of national integration which has been the stated goal of the country since its independence in 1957. As has been shown, those who really needs the functional requirement of the language either for educational or research purpose constitute only a small minority of the population. Thus the amount of money, manpower and time spent towards promoting the language could not justify for its continued existence in its present role. Under the present set up, the over emphasis given on the language prolongs the state of educational dependency of our country with its former colonial master. The result is that after years of independence we still fail to indentify ourselves with the outside world without relating ourselves to the standards and guidelines set up by Britain. The question that strikes me is that: Could we progress and develop without being trapped into the state of dependency